Radiographic incidence of femoral acetabular impingement in young adults - Barbati, Antonello; Pezzella, Raffaele; Silleni, Francesca; Magnani, Luca; Grattacaso, Giuseppe; Di Tunno, Valeria; Lombardi, Fabio Pasquale (Lo Scalpello - Journal, 2022)
After Ganz’s first work in 2003 on femoral acetabular impingement (FAI), the interest in this pathology has steadily increased. Several treatments have been proposed and many parameters have been evaluated to reach a diagnosis as accurate as possible. In fact, the resulting cartilage lesions are often associated with early development of osteoarthritis in symptomatic patients. Although there is a considerable percentage of elderly patients who meet radiographic criteria for FAI but are asymptomatic, this disease is commonly underestimated in young adults with coxalgia. The purpose of our study was to investigate these signs in radiographic images in patients under the age of 60 years who have undergone hip replacement surgery to see if FAI criteria were present. We found such signs in most of the patients examined. The most frequent type was mixed impingement. Diagnosis of FAI in symptomatic young adults, in the light of radiographic data, is likely to be underestimated. Early diagnosis and treatment therefore play a non-secondary role.